Optimization of Cu content for the development of high-performance T5-treated thixo-cast Al–7Si–0.5Mg–Cu (wt.%) alloy. (10th December 2021) - Yamamoto, K.; Takahashi, M.; Kamikubo, Y.; Sugiura, Y.; Iwasawa, S.; Nakata, T.; Kamado, S.
Highlights: The optimum Cu content is 0.5% in a T5-treated thixo-cast Al–7Si–0.5Mg alloy. The 0.5%Cu-containing alloy forms a high fraction of plate-like θ' phases. The formation of brittle Cu-rich phases is suppressed in the 0.5%Cu-containing alloy. The 0.5%Cu-containing alloy exhibits a good combination of strengths and ductility. Abstract: Cu content has been successfully optimized in a thixo-cast and directly aged (T5-treatment) Al–7Si–0.5Mg (wt.%) alloy. Even after the 0.5% Cu addition, plate-like Al2 Cu ( θ' ) phases, which contribute to high strengths and large plasticity, are precipitated. The formation of a large fraction of Cu-containing brittle phases could be suppressed as well. Then, the Al–7Si–0.5Mg–0.5Cu alloy exhibits high ultimate tensile strength, 0.2% proof stress, and elongation to failure of 296 MPa, 209 MPa, and 8.8%, respectively. This results in a high quality index similar to that of solution-treated and subsequently aged (T6-treated) Al–7Si–Mg alloys. A Cu addition over 1.0% further improves the strengths; however, this leads to poor ductility because of the high fraction of Cu-containing brittle phases.